Five novel bifidobacterial species isolated from faeces of primates in two Czech zoos: Bifidobacterium erythrocebi sp. nov., Bifidobacterium moraviense sp. nov., Bifidobacterium oedipodis sp. nov., Bifidobacterium olomucense sp. nov. and Bifidobacterium panos sp. nov. Issue 1 (23rd January 2021) - Neuzil-Bunesova, Vera; Lugli, Gabriele Andrea; Modrackova, Nikol; Vlkova, Eva; Bolechova, Petra; Burtscher, Johanna; Longhi, Giulia; Mancabelli, Leonardo; Killer, Jiri; Domig, Konrad; Ventura, Marco
Abstract : Five Bifidobacterium strains, VB23 T, VB24 T, VB25 T, VB26 T and VB31 T, were isolated from chimpanzee ( Pan troglodytes ), cotton-top tamarin ( Saguinus oedipus ), Goeldi's marmoset ( Callimico goeldii ), moustached tamarin ( Saguinus mystax ) and patas monkey ( Erythrocebus patas ), respectively, which were kept in two Czech zoos. These strains were isolated from faecal samples and were Gram-positive, non-motile, non-sporulating, anaerobic and fructose-6-phosphate phosphoketolase-positive. Phylogenetic analyses based on 16S rRNA revealed close relatedness between VB23 T and Bifidobacterium angulatum LMG 11039 T (96.0 %), VB24 T and Bifidobacterium pullorum subsp. pullorum DSM 20433 T (96.1 %), VB25 T and Bifidobacterium goeldii LMG 30939 T (96.5 %), VB26 T and Bifidobacterium imperatoris LMG 30297 T (98.1 %), and VB31 T and B . angulatum LMG 11039 T (99.40 %). Internal transcribed spacer profiling revealed that VB23 T, VB24 T, VB25 T, VB26 T and VB31 T had highest similarity to Bifidobacterium breve LMG 13208 T (77.2 %), Bifidobacterium longum subsp. infantis ATCC 15697 T (85.8 %), Bifidobacterium biavatii DSM 23969 T (76.9 %), B. breve LMG 13208 T (81.2 %) and B. angulatum LMG 11039 T (88.2 %), respectively. Average nucleotide identity (ANI) and digital DNA–DNA hybridization (dDDH) analyses with their closest neighbours supported the independent phylogenetic positions of the strains with values between 86.3 and 94.3 % for ANI and 25.8 and 54.9 % for dDDH. These genomic and phylogenetic analyses suggested that the evaluated strains were novel Bifidobacterium species named Bifidobacterium erythrocebi sp. nov. (VB31 T =DSM 109960 T =CCUG 73843 T ), Bifidobacterium moraviense sp. nov. (VB25 T =DSM 109958 T =CCUG 73842 T ), Bifidobacterium oedipodis sp. nov. (VB24 T =DSM 109957 T =CCUG 73932 T ), Bifidobacterium olomucense sp. nov. (VB26 T =DSM 109959 T =CCUG 73845 T ) and Bifidobacterium panos sp. nov. (VB23 T =DSM 109963 T =CCUG 73840 T ).